2021
DOI: 10.1111/aos.15078
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to the assessment and treatment of lamellar macular hole

Abstract: To analyse morpho-functional foveal changes in eyes with lamellar macular hole (LMH) by an integrated assessment of short-wavelength fundus autofluorescence (SW-FAF) and microperimetry (SW-FAF/microperimetry integrated assessment) before and after treatment with a technique of double-inverted flaps of epiretinal proliferation (EP) and internal limiting membrane (ILM). Methods: Clinical and tomographic parameters were best-corrected visual acuity (BCVA), LMH size, central retinal thickness (CRT) and outer retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…2E). The trend in retinal sensitivity changes confirms that inner retinal layers may contribute to visual performance with respect to the recognized role of photoreceptors in vitreoretinal surface disorders, as recent evidence suggested 9 …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…2E). The trend in retinal sensitivity changes confirms that inner retinal layers may contribute to visual performance with respect to the recognized role of photoreceptors in vitreoretinal surface disorders, as recent evidence suggested 9 …”
Section: Discussionsupporting
confidence: 75%
“…In this case report, the natural history of a spontaneous closure of an idiopathic full-thickness macular hole and its recurrence and reclosure detected by multimodal imaging will be discussed. The study evaluated the efficacy of a composite elaboration of short-wavelength fundus autofluorescence and microperimetry images to estimate the entity of damage seen by a topographical criterion (the superimposed method has been described in a previous published study) 9 . Moreover, the meaning of OCT and OCT-angiography changes over time, and both were studied by a quantitative and accurate method to test the retinal sensitivity and the macular function.…”
mentioning
confidence: 99%
“…As presented before, OCT plays an important role in the evaluation of LMH structure and morphology. Recent studies have shown interesting results using short-wavelength fundus autofluorescence (SW-FAF) [ 70 ] and microperimetry to assess retinal sensitivity (RS) [ 68 , 70 ]. Larger LMHs show hyper-FAF area combined to lower preoperative RS.…”
Section: Main Textmentioning
confidence: 99%
“…After surgery, the hyper-FAF area decreased, and RS increased. The reduction of FAF to physiological features is associated with higher RS and a whole functional improvement [ 70 ]. These further evaluations will help to better evaluate surgical indications for LMH.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation